Microsoft Office Excel 2010 : - Stewart, Kathleen (McGraw-Hill, 2011)
Presents an introduction of Microsoft Office 2010 skills. This title focuses on the introductory skills that are isolated in each lesson and then complete individual skill exercises that ensure a learning path.